Attacking Without Provocation; Maintaining a Subsequent Occupation; All for the Sake of Democratization: The Constitutionality and Wisdom of Preventive War and Post-Conflict Nation-Building - Kevin Green (Washington University Journal of Law & Policy, 2009)
This Note examines the constitutionality and wisdom of both aspects of the current warfare policy. Ultimately, the current United States warfare strategy that includes using preventive wars followed by post-conflict military nation-building is constitutional; however, underlying policy concerns suggest that this approach to warfare should be reconsidered and reframed.
Keywords: Military policy; Constitutional law; Nation building; Bush doctrine; Democratization; Military intervention; Postwar reconstruction; Preemption (Military doctrine); International